Proactive In-Water Ship Hull Grooming as a Method to Reduce the Environmental Footprint of Ships - Swain, Geoffrey; Erdogan, Caglar; Foy, Lauren; Gardner, Harrison; Harper, Michael; Hearin, John; Hunsucker, Kelli Z.; Hunsucker, J. Travis; Lieberman, K.; Nanney, Mark; Ralston, Emily; Stephens, Abraham; et al. (Frontiers in Marine Science, 2022)
Improved management of ship hull coatings provides an opportunity to address the climate crisis, invasive species and the discharge of biocides into the marine environment. A large percentage of the total power required to propel a ship is to overcome the viscous drag created between the hull and the water. The powering penalty due to increases in coating roughness and the development of biofouling are well documented. In addition poorly maintained fouling control coatings may lead to the transportation of invasive species and in-water cleaning create the discharge of excess amounts of biocides and microplastics. In-water hull cleaning is an important part of ship operations, however, this is typically implemented as a reactive measure when fouling reaches a critical level and requires powerful machinery, may damage the coatings, creates unwanted discharge and in many locations the discharge will require capture and disposal. Ship hull grooming is being developed as a proactive method to manage fouling control coatings that will ensure that they are maintained in a smooth and fouling free condition, there is no transport of invasive species or excessive discharge of material that occurs during cleaning. This paper will summarize the findings of many years of research and development.